Efektivitas Kinerja Badan Penanggulangan Bencana Daerah Kota Semarang Berbasis Early Warning System - Selly Intani Syahputri; Rahmawati Husein (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2023)
This study describes the effectiveness of the performance of the Semarang City Regional Disaster Management Agency (BPBD) in flood disaster management based on the Early Warning System (EWS). The research method is qualitative with a descriptive approach which will be studied with indicators of effectiveness, namely goal attainment, integration, and adaptation. The research findings show that in carrying out the achievement of objectives, Semarang City BPBD has referred to the strategic plan that is in accordance with the Vision and Mission of Semarang City RPJMD 2016-2021. The implementation of the socialization process has gone well, Semarang City BPBD held meetings with the KSB (Disaster Alert Village) directly or via WhatsApp, then there was communication with other OPDs if there were problems with the EWS. The adaptation of Semarang City BPBD in flood disaster management using EWS technology as disaster prevention and preparedness has been optimal, through training activities to increase employee capacity in operating EWS technology.